Fear of pain in pediatric headache. (January 2015) - Simons, Laura E; Pielech, Melissa; Cappucci, Stefanie; Lebel, Alyssa
Objective: The current study provides the first measure of pain-related fear for pediatric headache patients. Methods: From a large pediatric headache clinic, a cross-sectional cohort of 206 children and adolescents completed measures of pain-related fear, anxiety sensitivity, catastrophizing, pain acceptance, functional disability, and school functioning. Results: The two-factor solution of the Fear of Pain Questionnaire (FOPQ) was confirmed from the originally derived structure with pediatric headache patients. Simultaneously regressing FOPQ subscales fear of pain and activity avoidance on theorized construct validity measures demonstrated that fear of pain was more closely linked with anxiety sensitivity and pain catastrophizing while activity avoidance had a strong negative association with pain acceptance (activity engagement and pain willingness). Pain-related fear was not significantly associated with pain level. After controlling for demographic factors and pain, fear of pain and activity avoidance accounted for an additional 26% of the variance in functional disability and school functioning outcomes, with activity avoidance accounting for much of this relationship. Conclusions: Although typically considered an influential construct among musculoskeletal patients, pain-related fear is also an important factor influencing functioning among pediatric headache patients, with the dimension of activity avoidance particularly salient.